Prenatal Low-Protein and Low-Calorie Diets Differentially Alter Arcuate Nucleus Morphology in Newborn Male Rats - Blanco, Noemí; Fernández-García, Jose Manuel; Carrillo, Beatriz; Ballesta, Antonio; García-Úbeda, Rocío; Collado, Paloma; Pinos, Helena (Frontiers in Neuroanatomy, 2022)
Background Malnutrition during the early stages of development produces alterations that can compromise the functioning of the hypothalamic circuits that regulate food intake. The purpose of this study is to analyze the effects that a low-protein and low-calorie diet has on the morphology of the arcuate nucleus (ARC) of the hypothalamus in newborn male and female rats. Methods On gestational day 6 (G6), six pregnant rats were divided into two groups. One group was made up of three pregnant rats, which were fed ad libitum with a control diet (20% casein), and the other one was made up of three pregnant rats, which were fed ad libitum with a low-protein diet (8% casein) and 30% of a calorie-restricted diet. On the day of birth, pups were sacrificed, resulting in four experimental groups: control male, control female, low-protein and low-calorie diet male, and low-protein and low-calorie diet female (n = 5 in each group). The volume and number of neurons, together with the neuronal density and number of apoptotic cells, were measured. Results Males on a low-protein and low-calorie diet showed a significant increase in the number of neurons and in the neuronal density of the ARC with regard to the rest of the groups studied. These increases were also reflected in the posterior part of the nucleus. Although the existence of sexual dimorphism was not detected in any of the parameters studied in the control groups, the number of neurons and neuronal density showed differences between males and females fed with a low-protein and low-calorie diets due to the increase in the number of neurons shown by the male. No significant differences were found in the number of apoptotic cells. Conclusion Our results show that a low-protein and low-calorie diet during the prenatal stage produces alterations in the ARC of the hypothalamus in newborn animals and, more importantly, that the effects of malnutrition are evident in males but not in females. Therefore, it is essential to follow a balanced diet during the early stages of life to ensure optimal development of the neural circuits that regulate eating.